TEM-based dislocation tomography: Challenges and opportunities. Issue 3 (June 2020) - Feng, Zongqiang; Fu, Rui; Lin, Chengwei; Wu, Guilin; Huang, Tianlin; Zhang, Ling; Huang, Xiaoxu
Highlights: 3D TEM quantitative characterization of dislocations are reviewed. Tomographic crystallography enables integrated characterization of dislocations. Challenges and opportunities in TEM-based dislocation tomography are summarized. Abstract: Dislocation tomography based on transmission electron microscopy (TEM) exhibits excellent capabilities in three dimensional (3D) visualization of various dislocation structures but still suffers from poor quantification and coupling between the geometry and crystallography of dislocations. In the present paper, we review the research on 3D quantitative characterization of dislocation structures using TEM-based dislocation tomography and stereo pair methods, and briefly introduce a novel TEM-based tomographic crystallography method which can simultaneously and quantitatively characterize the geometric and crystallographic features of dislocations. We summarize some technical problems and challenges in the workflow of TEM-based dislocation tomography, including image contrast optimization, irradiation damage, image processing, reconstruction algorithms as well as dislocation segmentation and identification. We further discuss the potential applications of TEM-based dislocation tomography and envisage several promising approaches for developing an advanced four-dimensional (4D) dislocation characterization technique.